LANGUAGE CHOICE AND ATTITUDE IN ENGLISH CLASSROOM: A STUDY ON LANGUAGE AND SOCIAL IDENTITY - D.P.N.P. Sari; N.L.P.S. Adnyani; N.L.P.E. Dewi (LPSDI Bina Patria, 2024)
The purpose of this study was: 1) To explore the language choice of the students when interacting with the teachers in English classroom. 2) To explore the language choice of the students when interacting with peers during English class. 3) To investigate the language choice of the students outside the classroom. 4) To investigate the students’ language attitude towards English. This investigation was conducted at SMP AMI Denpasar. The methodology of this study was descriptive qualitative method with a case study research design. The participant consists of 77 students. The data were obtained by employed interview guide, questionnaire sheet, and observation sheet. The finding indicated that, 1) there was the highest score 71,4%. The students mostly used mixed Indonesian-English as a tool of communication when they interact with their teacher during English class. 2) there was 46,8%. the students who speak mixed Indonesian-English in the class. In the other hand, the students who still had lack to use English they will mix into Indonesian to avoid misunderstandings. 3) the highest score for language choice was Indonesian. One of the results was 76,6% for language use with the teacher outside the English class. 4) the highest score for students’ attitude towards English-Indonesian was 72%. It reflected that students have positive attitudes regarding to English and Indonesian languages. Participants want to demonstrate it all when taking part in English-language activities. In conclusion, these days local languages are barely spoken among the younger generation. Since English is the most used language in daily life. Therefore, they chose to obtain acceptance from people in their surroundings.